Dendrimer ligands-capped CH3NH3PbBr3 perovskite nanocrystals with delayed halide exchange and record stability against both moisture and water. (12th April 2018) - Xu, Yiren; Xu, Shuhong; Shao, Haibao; Jiang, Han; Cui, Yiping; Wang, Chunlei
Abstract: CH3 NH3 PbBr3 perovskite nanocrystals (NCs) suffer from poor stability because of their high sensitivity to environmental moisture and water. To solve this problem, previous works mainly focus on embedding perovskite NCs into water-resistant matrix to form large composites (size of microns or larger). As an alternative solution without serious changing of NC size, enhancing the stability of perovskite NCs themselves by ligand engineering is rarely reported. In this work, we used hyperbranched polyamidoamine (PAMAM) dendrimers with two different generations (G0 and G4) to synthesize CH3 NH3 PbBr3 perovskite NCs with high photoluminescence (PL) quantum yields (QY) above 70% and a new record stability. A novel dendrimers generation-dependent stability of perovskite NCs was observed. The water-resistance time is 18 h (27 h) for perovskite NCs capped by G0 (G4) generation of PAMAM, which is 7 times (11 times) longer than that of traditional oleic acid-capped NCs. Similar PAMAM generation-related stability is also observed in moisture-resistance tests. The stability time against moisture is 500 h (800 h) for G0 (G4) generation of PAMAM-capped perovskite NCs, which is a new record stability time against moisture for CH3 NH3 PbBr3 perovskite NCs. In addition, our results also indicate that PAMAM ligands outside perovskite NCs can dramatically slow down the speed of halide exchange. Even for the mixture of perovskite NCs with two different halide composition, the original luminescence properties of PAMAM-capped perovskite NCs can retain after mixing. In view of slow halide exchange speed, excellent water and moisture stability, PAMAM dendrimers-capped perovskite NCs and their mixture are available as color conversion single layer in fabrication of light-emitting diodes (LED).